Preparation method of silica sol shell for Al2O3 fiber modification of polycrystalline casting

By using Al2O3 fiber modified silicon sol slurry and Al2O3 fiber mullite as the back layer material of the mold shell, the existing problems of low strength and low production efficiency of the silicon sol type shell are solved, and the casting accuracy and yield increase are achieved.

CN119500975APending Publication Date: 2025-02-25RED SILVER METAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411660462.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing silicon sol shell has low strength at room temperature and high temperature, slow drying speed and low production efficiency, resulting in low casting accuracy and reduced yield.

Method used

Silica sol slurry modified with Al2O3 fiber is used as the back layer, and mullite mixed with Al2O3 fiber is used as the back layer sand-spreading material. The Al2O3 fiber is closely combined with mullite through sintering to strengthen the strength of the shell, and suppress cracking and deformation.

Benefits of technology

The room temperature and high temperature strength of the molded shell are improved, the casting accuracy and metallurgical quality of the castings are improved, the yield rate is increased, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500975A_ABST
    Figure CN119500975A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a silica sol shell for Al2O3 fiber modification of a polycrystalline casting, and belongs to the technical field of precision casting. According to the preparation method, Al2O3 fiber modified silica sol slurry is adopted as back layer slurry, and Al2O3 fiber mixed mullite is adopted as a back layer sanding material to prepare the silica sol mold shell. The Al2O3 fibers are added into the back layer of the silica sol shell, so that the growth of continuous cracks in the silica sol shell can be inhibited, the binding force of mullite sand grains and slurry is improved, the strength of the silica sol shell is improved, cracking and deformation of the shell are effectively improved, meanwhile, the air permeability can be slightly improved, and the application of the Al2O3 fibers in the shell preparation process is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of precision casting of polycrystalline castings of aircraft engines, and in particular provides a method for preparing an Al2O3 fiber-modified silica sol shell of a polycrystalline casting. Background Art

[0002] Precision casting is also known as investment casting and lost wax casting. This method can be used to produce castings with complex shapes, and has the advantages of high casting accuracy and surface quality. Due to its excellent process advantages, this method has been widely used in the field of aviation industry manufacturing. Precision casting can obtain castings with smooth surface and accurate size, which is directly related to the quality of the mold shell. The quality of the mold shell is mainly affected by the shell material and shell making process. At present, the mold shell commonly used in production is mostly silica sol mold shell. However, silica sol mold shell has the disadvantages of low strength at room temperature and high temperature, slow drying speed, and low production efficiency.

[0003] In order to solve the defects of silica sol mold shell in the prior art, the present invention provides a method for preparing Al2O3 fiber modified silica sol mold shell for polycrystalline castings, and proposes to use Al2O3 fiber modified silica sol slurry as a back layer and mullite mixed with Al2O3 fibers as a back layer sanding material to strengthen the room temperature and high temperature strength of the mold shell, improve the air permeability, improve the metallurgical quality and dimensional accuracy of the casting, achieve an increase in the yield and reduce the cost. Summary of the invention

[0004] In order to solve the problems existing in the current silica sol mold shell, the purpose of the present invention is to provide a method for preparing an Al2O3 fiber-modified silica sol mold shell for polycrystalline castings, by using Al2O3 fiber-modified silica sol slurry as a back layer, and mullite mixed with Al2O3 fibers as a sanding material for the back layer of the mold shell, and by sintering, the Al2O3 fibers and mullite are tightly combined to strengthen the mold shell strength, inhibit the cracking and deformation of the mold shell, and improve the low casting precision of polycrystalline castings caused by the deformation of the ceramic mold shell.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A method for preparing a silica sol shell for polycrystalline castings modified with Al2O3 fibers, the method comprising the following steps:

[0007] (1) preparing a surface layer, a transition layer and a back layer slurry, wherein the back layer slurry is a silica sol slurry modified with Al2O3 fibers, and the back layer slurry comprises mullite, silica sol and Al2O3 fibers; wherein the weight ratio of Al2O3 fibers to silica sol is (0.005-0.015):1; the weight ratio of mullite to silica sol is (1-2):1; the Al2O3 fibers are polycrystalline Al2O3, the fiber diameter is 2-20 μm, the fiber length is 40-200 μm, the particle size of the mullite is 180-220 mesh, and the silica sol is 1030 type silica sol;

[0008] (2) Preparation of the shell surface layer, transition layer and back layer and sealing and drying;

[0009] (3) The shell is dewaxed and calcined to obtain a silica sol ceramic shell modified with Al2O3 fibers for polycrystalline castings.

[0010] Furthermore, the raw materials of the surface slurry are EC95 powder, cobalt aluminate powder, silica sol, defoamer and wetting agent. Among them, EC95 powder and cobalt aluminate powder are powders, the weight ratio of EC95 powder to cobalt aluminate powder in the powder is 7: (1.5-3.5), the weight ratio of silica sol to powder is 1: (3-4), the weight ratio of defoamer to silica sol is (0.002-0.004): 1, the weight ratio of wetting agent to silica sol is (0.002-0.004): 1, the particle size of EC95 powder used in the surface slurry is 300-340 mesh, the particle size of cobalt aluminate powder is greater than 600 mesh, and the silica sol is 830 type silica sol.

[0011] Furthermore, the preparation process of the surface slurry is as follows: after the raw materials are placed in a slurry barrel and mixed, a high-speed disperser is used for stirring at a stirring speed of 280-350 rpm for a stirring time of more than 24 hours. The surface slurry uses deionized water to adjust the slurry viscosity within the range of 30 to 40 seconds.

[0012] Furthermore, the raw materials of the transition layer slurry are corundum powder, defoamer, reinforcing agent and silica sol. The weight ratio of corundum powder to silica sol is (2-3):1, the weight ratio of defoamer to silica sol is (0.002-0.004):1, and the weight ratio of reinforcing agent to silica sol is (0.05-0.1):1. The particle size of the corundum powder used in the transition layer slurry is 300-340 mesh, and the reinforcing agent is polyvinyl alcohol with a molecular weight of 10,000-200,000.

[0013] Furthermore, in the process of preparing the transition layer and back layer slurry, the slurry raw materials are mixed in a slurry barrel and stirred with a high-speed disperser at a stirring speed of 280-350 rpm for more than 12 hours. The viscosity of the transition layer slurry and the back layer slurry is regulated within 10-20 seconds using deionized water.

[0014] Furthermore, the sanding material used in the preparation of the shell surface layer is corundum sand with a particle size of 80-120 meshes. The sanding material used in the preparation of the transition layer is corundum sand with a particle size of 50-70 meshes. The sanding material used in the preparation of the back layer is mullite mixed with Al2O3 fibers with a particle size of 15-30 meshes. The weight ratio of Al2O3 fiber to mullite is (0.005-0.01): 1. The Al2O3 fiber is polycrystalline Al2O3 with a fiber diameter of 2-20 microns and a fiber length of 40-200 microns.

[0015] Furthermore, the drying process in the shell preparation of step (2) is as follows:

[0016] The surface layer is naturally dried for 1-1.5 hours at a temperature of 21-25°C and a humidity of 60-80%. The transition layer and the back layer are blow-dried for 2-3 hours at a temperature of 21-25°C and a humidity of 40-60% with a wind speed of 4-9m / s. The sealing layer is naturally dried for more than 48 hours at a temperature of 21-25°C and a humidity of 40-60%.

[0017] Furthermore, the shell is dewaxed using a high-pressure steam dewaxing kettle, the dewaxing temperature is 170-200°C, the dewaxing pressure is 7.9-8.4 bar, and the dewaxing time is 10-20 minutes.

[0018] Furthermore, the shell is fired in a trolley-type gas furnace, the heating rate is 8-10°C / min, the insulation temperature is 950-970°C, the insulation time is 2-3h, and the shell is cooled to below 300°C before being taken out of the furnace.

[0019] Compared with the prior art, the advantages of the present invention application are: the present invention patent adopts the method of using Al2O3 fiber modified silica sol slurry as the back layer slurry and mullite mixed with Al2O3 fiber as the back layer sanding material, and suppresses the growth of continuous cracks inside the silica sol shell by Al2O3 fiber, improves the bonding force between mullite sand and slurry, enhances the sintering strength of the modified shell, and promotes the application of Al2O3 fiber in the shell preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Surface quality comparison of the pouring cup of comparative example 1 and embodiment 1, wherein A is the surface quality of the mold shell pouring cup prepared in comparative example 1, and B is the surface quality of the mold shell pouring cup prepared in embodiment 1.

[0021] Figure 2 The figure is a comparison of the difference between the actual and theoretical dimensions of the castings of Examples 1-3 and Comparative Example 1.

[0022] Figure 3 The following is a comparison of the shell expansion and inclusion failure rates of the castings prepared in Comparative Example 1 and Examples 1-3.

[0023] Figure 4 The high temperature strength and room temperature strength of the castings prepared in comparative example 1 and examples 1-3 are compared. DETAILED DESCRIPTION

[0024] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0025] Example 1

[0026] This embodiment prepares a silica sol mold shell for a polycrystalline blade of an aeroengine according to the following steps:

[0027] (1) Preparation of surface layer, transition layer and back layer slurry,

[0028] Preparation of surface slurry: weigh the surface slurry raw materials according to the following mass ratio: 830 type silica sol: powder: defoamer: wetting agent = 1:3.5:0.003:0.003; the powder is 320#EC95 powder and 800#cobalt aluminate powder in a weight ratio of 7:3,

[0029] The specific preparation process of the surface layer slurry is as follows: place the required 830 type silica sol in a slurry mixing barrel, set the stirring speed to 280 rpm, then add the required wetting agent 7667 (NALCO), stir for 10 minutes, then slowly add the required powder to the slurry barrel in 3 times while stirring, stir for 10 minutes after each addition of powder before adding the next powder, stir for 30 minutes after the powder is added, finally add the required defoaming agent 2305 (NALCO), use deionized water to adjust the slurry viscosity to 35±5s, and the slurry can be used after stirring for 24 hours.

[0030] Preparation of transition layer slurry: Weigh the transition layer slurry raw materials according to the following mass ratio: 1030 type silica sol: 320# corundum powder: defoamer: polyvinyl alcohol (molecular weight 100,000) = 1:2.4:0.003:0.05;

[0031] The specific preparation process of the transition layer slurry is as follows: place the required 1030 type silica sol in the slurry stirring barrel, set the stirring speed to 280 rpm, then slowly add 320# corundum powder into the slurry barrel while stirring, after stirring for 30 minutes, add the required polyvinyl alcohol, stir for 10 minutes, and finally add defoamer 2305 (NALCO), use deionized water to adjust the slurry viscosity to 15±5s, and the slurry can be used after stirring for 12 hours.

[0032] Preparation of back layer slurry: weigh the back layer slurry raw materials according to the following mass ratio; 1030 type silica sol: 200# mullite: Al2O3 fiber = 1:1.7:0.008, Al2O3 fiber is polycrystalline Al2O3, fiber diameter is 12 microns, and fiber length is 80 microns.

[0033] The specific preparation process of the back layer slurry is as follows: place the required 1030 type silica sol in the slurry stirring barrel, set the stirring speed to 280 rpm, then slowly add 200# mullite into the slurry barrel while stirring, after stirring for 30 minutes, add the required Al2O3 fiber, use deionized water to adjust the slurry viscosity to 15±5s, and the slurry can be used after stirring for 12 hours.

[0034] (2) Shell preparation

[0035] The spare wax mold module is used to prepare the shell surface layer, transition layer and back layer and seal and dry the shell. The shell preparation process is shown in Table 1;

[0036] Table 1 Shell preparation process

[0037]

[0038] The weight ratio of Al2O3 fiber to 16-30 mesh mullite in the back layer sand-sprinkling material is 0.008:1.

[0039] (3) The shell is dewaxed and calcined to obtain a silica sol ceramic shell modified with Al2O3 fibers for polycrystalline castings.

[0040] The shell prepared in step (2) was dewaxed using a high-pressure steam dewaxing kettle at a dewaxing temperature of 190° C., a dewaxing pressure of 8.2 bar, and a dewaxing time of 15 min.

[0041] The dewaxed shell was fired in a trolley-type gas furnace at a heating rate of 8.5°C / min, a holding temperature of 950°C, and a holding time of 2h. The shell was cooled to below 300°C and then taken out of the furnace to obtain a silica sol ceramic shell modified with Al2O3 fibers for polycrystalline castings.

[0042] A high-temperature alloy liquid is poured into the cavity of the calcined silica sol ceramic shell, wherein the shell preheating temperature is 980° C. and the pouring temperature is 1450° C., to obtain a casting.

[0043] The composition of the high-temperature alloy liquid is as follows: carbon: 0.047wt%, chromium: 11.63wt%, molybdenum: 4.13wt%, niobium: 2.01wt%, titanium: 0.68wt%, boron: 0.011wt%, aluminum: 5.84wt%, zirconium: 0.093wt%, iron: 0.014wt%, magnesium: 0.003wt%, manganese: 0.002wt%, silicon: 0.01wt%, phosphorus: 0.002wt%, copper 0.01wt%, cobalt: 0.01wt%, sulfur 0.0002wt%, and the balance is nickel.

[0044] In this embodiment, 8 molds and 48 castings were prepared, of which 2 castings had inclusions and 2 castings had shell expansion.

[0045] The shell mold prepared by the method of the embodiment has a surface layer at the pouring cup that does not fall off after dewaxing and roasting, and has a high surface finish. Figure 1 As shown in the figure, the metallurgical quality of the prepared castings is improved. The leakage ratio is reduced when the shell leaks sideways, and the shell cracking is improved. Two castings are randomly selected from each module to measure the blade length and root thickness, and the average value of the difference between the actual casting size and the theoretical size is calculated, as shown in Figure 2 As shown, the prepared casting state is highly consistent with the wax part, the difference between the actual size and the theoretical size of the casting is reduced, and the degree of shell deformation is improved.

[0046] Comparative Example 1

[0047] The same polycrystalline casting silica sol shell as in Example 1 was prepared. The difference from Example 1 was that the back layer slurry did not contain Al2O3 fibers, and the sanding material used in the preparation of the back layer of the shell was different.

[0048] (1) preparing surface layer, transition layer and back layer slurry;

[0049] Preparation of surface layer slurry: weigh the surface layer slurry raw materials according to the following mass ratio; 830 type silica sol: powder: defoaming agent: wetting agent = 1:3.5:0.003:0.003; wherein the powder is 320#EC95 powder and greater than 600#cobalt aluminate powder in a weight ratio of 7:3; the specific preparation process of the slurry is the same as Example 1.

[0050] Preparation of transition layer slurry: Weigh the transition layer slurry raw materials according to the following mass ratio; 1030 type silica sol: 320# corundum powder: defoamer: polyvinyl alcohol (molecular weight 100,000) = 1:2.4:0.003:0.05; the specific preparation process of the slurry is the same as Example 1.

[0051] Preparation of back layer slurry: Weigh the back layer slurry raw materials according to the following mass ratio: 1030 type silica sol: 200# mullite = 1:1.7. The specific preparation process of the slurry is the same as Example 1, and the step of adding Al2O3 fiber is omitted.

[0052] (2) Shell preparation

[0053] A spare wax mold module is used to prepare the shell surface layer, transition layer and back layer and seal and dry the shell. The shell preparation process is shown in Table 2; the difference from Example 1 is that the back layer sanding material does not contain 16-30 mesh mullite and does not contain Al2O3 fiber.

[0054] Table 2 Shell preparation process

[0055]

[0056] (3) The shell is dewaxed and sintered to obtain a silica sol ceramic shell for polycrystalline castings.

[0057] The shell prepared in step (2) is dewaxed in a high-pressure steam kettle at a dewaxing temperature of 190° C., a dewaxing pressure of 8.2 bar, and a dewaxing time of 15 min.

[0058] The dewaxed shell is fired in a trolley-type gas furnace at a heating rate of 10°C / min, a holding temperature of 950°C, a holding time of 2h, and is then taken out of the furnace after cooling to below 300°C.

[0059] The same high temperature alloy liquid as in Example 1 was poured into the calcined silica sol ceramic shell cavity, wherein the shell preheating temperature was 980° C. and the pouring temperature was 1450° C. to obtain a casting. In this comparative example, 48 castings were prepared from 8 molds, of which 7 castings had inclusions and 6 castings had shell expansion.

[0060] The shell prepared by this method has the surface layer falling off at the pouring cup and the surface finish is low. Figure 1 As shown in A, the surface of the prepared casting has defects such as ceramic inclusions, sand holes, and shell expansion. In addition, the prepared casting has blade distortion and dimensional tolerance.

[0061] Example 2

[0062] The same polycrystalline casting silica sol shell as in Example 1 was prepared. The difference from Example 1 was that the Al2O3 fiber content in the back layer slurry was different, and the Al2O3 fiber content in the sanding material used in the preparation of the shell back layer was different.

[0063] (1) Preparation of surface layer, transition layer and back layer slurry,

[0064] Preparation of surface layer slurry: weigh the surface layer slurry raw materials according to the following mass ratio; 830 type silica sol: powder: defoaming agent: wetting agent = 1:3.5:0.003:0.003; wherein the powder is 320#EC95 powder and 800#cobalt aluminate powder in a weight ratio of 7:3. The specific preparation process of the slurry is the same as Example 1.

[0065] Preparation of transition layer slurry: Weigh the transition layer slurry raw materials according to the following mass ratio; 1030 type silica sol: 320# corundum powder: defoamer: polyvinyl alcohol (molecular weight 100,000) = 1:2.4:0.003:0.05; the specific preparation process of the slurry is the same as Example 1.

[0066] Preparation of back layer slurry: weigh the back layer slurry raw materials according to the following mass ratio; 1030 type silica sol: 200# mullite: Al2O3 fiber = 1:1.7:0.005, Al2O3 fiber is polycrystalline Al2O3, fiber diameter is 12 microns, fiber length is 80 microns; the specific preparation process of the slurry is the same as Example 1.

[0067] (2) Shell preparation

[0068] The spare wax mold module is used to prepare the shell surface layer, transition layer and back layer and seal and dry the shell. The shell preparation process is shown in Table 3;

[0069] Table 3 Shell preparation process

[0070]

[0071] The weight ratio of Al2O3 fiber to 16-30 mesh mullite in the back layer sand-sprinkling material is 0.005:1.

[0072] (3) The shell is dewaxed and calcined to obtain a silica sol ceramic shell modified with Al2O3 fibers for polycrystalline castings.

[0073] The shell prepared in step (2) was dewaxed using a high-pressure steam dewaxing kettle at a dewaxing temperature of 190° C., a dewaxing pressure of 8.2 bar, and a dewaxing time of 15 min.

[0074] The dewaxed shell was fired in a trolley-type gas furnace at a heating rate of 8.5°C / min, a holding temperature of 950°C, and a holding time of 2h. The shell was cooled to below 300°C and then taken out of the furnace to obtain a silica sol ceramic shell modified with Al2O3 fibers for polycrystalline castings.

[0075] The same high temperature alloy liquid as in Example 1 was poured into the calcined silica sol ceramic shell cavity, wherein the shell preheating temperature was 980° C. and the pouring temperature was 1450° C. to obtain a casting. In this example, 48 castings were prepared from 8 molds, of which 4 castings had inclusions and 3 castings had shell expansion.

[0076] The shell mold prepared by the method of this embodiment has no surface layer falling off at the pouring cup after dewaxing and roasting, and the surface finish is high, and the metallurgical quality of the prepared casting is improved. The leakage ratio is reduced when the shell mold leaks sideways, and the cracking of the shell mold is improved. The state of the prepared casting is highly consistent with the wax part, the difference between the actual size of the casting and the theoretical size is reduced, and the deformation degree of the shell mold is improved.

[0077] Example 3

[0078] The same polycrystalline casting silica sol shell as in Example 1 was prepared. The difference from Example 1 was that the Al2O3 fiber content in the back layer slurry was different, and the Al2O3 fiber content in the sanding material used in the preparation of the shell back layer was different.

[0079] (1) Preparation of surface layer, transition layer and back layer slurry,

[0080] Preparation of surface layer slurry: weigh the surface layer slurry raw materials according to the following mass ratio; 830 type silica sol: powder: defoaming agent: wetting agent = 1:3.5:0.003:0.003; wherein the powder is 320#EC95 powder and 800#cobalt aluminate powder in a weight ratio of 7:3. The specific preparation process of the slurry is the same as Example 1.

[0081] Preparation of transition layer slurry: Weigh the transition layer slurry raw materials according to the following mass ratio: 1030 type silica sol: 320# corundum powder: defoamer: polyvinyl alcohol = 1:2.4:0.003:0.05; the specific preparation process of the slurry is the same as Example 1.

[0082] Preparation of back layer slurry: weigh the back layer slurry raw materials according to the following mass ratio; 1030 type silica sol: 200# mullite: Al2O3 fiber = 1:1.7:0.01, Al2O3 fiber is polycrystalline Al2O3, fiber diameter is 12 microns, fiber length is 80 microns; the specific preparation process of the slurry is the same as Example 1.

[0083] (2) Shell preparation

[0084] The spare wax mold module is used to prepare the shell surface layer, transition layer and back layer and seal and dry the shell as shown in Table 1; the shell preparation process in Table 1 is as follows:

[0085]

[0086] The weight ratio of Al2O3 fiber to 16-30 mesh mullite in the back layer sand-sprinkling material is 0.01:1.

[0087] (3) The shell is dewaxed and calcined to obtain a silica sol ceramic shell modified with Al2O3 fibers for polycrystalline castings.

[0088] The shell prepared in step (2) was dewaxed using a high-pressure steam dewaxing kettle at a dewaxing temperature of 190° C., a dewaxing pressure of 8.2 bar, and a dewaxing time of 15 min.

[0089] The dewaxed shell was fired in a trolley-type gas furnace at a heating rate of 8.5°C / min, a holding temperature of 950°C, and a holding time of 2h. The shell was cooled to below 300°C and then taken out of the furnace to obtain a silica sol ceramic shell modified with Al2O3 fibers for polycrystalline castings.

[0090] The same high temperature alloy liquid as in Example 1 was poured into the calcined silica sol ceramic shell cavity, wherein the shell preheating temperature was 980° C. and the pouring temperature was 1450° C. to obtain a casting. A total of 48 castings were prepared in this example, of which 2 had inclusions and 1 had a bulged shell.

[0091] The shell prepared by the method of comparative example 3 has no surface layer falling off at the pouring cup after dewaxing and roasting, and the surface finish is high, and the metallurgical quality of the prepared casting is improved. The leakage ratio is reduced when the shell leaks sideways, and the cracking of the shell is improved. The state of the prepared casting is highly consistent with the wax part, the difference between the actual size of the casting and the theoretical size is reduced, and the deformation degree of the shell is improved.

[0092] from Figure 1 It can be seen that the difference between the actual size and the theoretical size of the casting prepared by adding Al2O3 fiber to the shell is reduced. With the increase of Al2O3 fiber addition, the difference between the actual size and the theoretical size of the casting is reduced. Figure 3 It shows that the proportion of shell expansion on the casting surface decreases with the increase of Al2O3 fiber content. This is because the addition of Al2O3 fiber improves the high-temperature strength of the shell, reduces the degree of deformation of the shell at high temperature, and the surface of the casting does not expand or exceed the size. Figure 2 It can be seen that the shell prepared using the embodiment method has partially improved room temperature strength, but the effect of improving high temperature strength is small, the surface layer at the pouring cup has not fallen off, and the surface finish is high. During the inspection process, it was found that the surface and internal inclusions of the prepared casting were reduced, the leakage ratio was reduced when the shell leaked sideways, the cracking of the shell was improved, and the metallurgical quality of the casting was improved.

Claims

1. A method for preparing a silica sol shell for polycrystalline castings modified with Al2O3 fibers, characterized in that: (1) preparing a surface layer, a transition layer and a back layer slurry, wherein the back layer slurry is a silica sol slurry modified with Al2O3 fibers, and the back layer slurry comprises mullite, silica sol and Al2O3 fibers; wherein the weight ratio of Al2O3 fibers to silica sol is (0.005-0.015):1; the weight ratio of mullite to silica sol is (1-2):1; the Al2O3 fibers are polycrystalline Al2O3, the fiber diameter is 2-20 μm, and the fiber length is 40-200 μm; (2) Preparation of the shell surface layer, transition layer and back layer and sealing and drying; (3) The shell is dewaxed and calcined to obtain a silica sol ceramic shell modified with Al2O3 fibers for polycrystalline castings.

2. The preparation method according to claim 1, characterized in that: The mullite particle size used in the back layer slurry is 180-220 meshes, and the silica sol is 1030 type silica sol.

3. The preparation method according to claim 1, characterized in that: The raw materials of the surface layer slurry are EC95 powder, cobalt aluminate powder, silica sol, defoaming agent and wetting agent; wherein, EC95 powder and cobalt aluminate powder are powders, the weight ratio of EC95 powder to cobalt aluminate powder in the powder is 7:(1.5-3.5), the weight ratio of silica sol to powder is 1:(3-4), the weight ratio of defoaming agent to silica sol is (0.002-0.004):1, the weight ratio of wetting agent to silica sol is (0.002-0.004):1, the EC95 powder used in the surface layer slurry has a particle size of 300-340 mesh, the cobalt aluminate powder has a particle size greater than 600 mesh, and the silica sol is 830 type silica sol.

4. The preparation method according to claim 1, characterized in that: The raw materials of the transition layer slurry are corundum powder, defoamer, reinforcing agent and silica sol; the weight ratio of corundum powder to silica sol is (2-3):1, the weight ratio of defoamer to silica sol is (0.002-0.004):1, and the weight ratio of reinforcing agent to silica sol is (0.05-0.1):1; the particle size of the corundum powder used in the transition layer slurry is 300-340 mesh, and the reinforcing agent is polyvinyl alcohol with a molecular weight of 10,000-200,000.

5. The preparation method according to claim 1, characterized in that: The viscosity of the surface layer slurry is 35±5s; the viscosity of the transition layer slurry and the back layer slurry is 15±5s.

6. The preparation method according to claim 1, characterized in that: The sanding material used in the preparation of the surface layer is corundum sand with a particle size of 80-120 meshes, the sanding material used in the preparation of the transition layer is corundum sand with a particle size of 50-70 meshes, and the sanding material used in the preparation of the back layer is mullite mixed with Al2O3 fiber, the particle size of mullite is 15-30 meshes, and the weight ratio of Al2O3 fiber to mullite is (0.005-0.01):

1.

7. The preparation method according to claim 1, characterized in that: The drying process in the shell preparation of step (2) is as follows: The surface layer is naturally dried for 1-1.5 hours at a temperature of 21-25°C and a humidity of 60-80%. The transition layer and the back layer are blow-dried for 2-3 hours at a temperature of 21-25°C and a humidity of 40-60% with a wind speed of 4-9m / s. The sealing layer is naturally dried for more than 48 hours at a temperature of 21-25°C and a humidity of 40-60%.

8. The preparation method according to claim 1, characterized in that: The shell dewaxing in step (3) adopts a high-pressure steam dewaxing kettle, the dewaxing temperature is 170-200°C, the dewaxing pressure is 7.9-8.4 bar, and the dewaxing time is 10-20 minutes.

9. The preparation method according to claim 1, characterized in that: In step (3), the medium-sized shell is fired in a trolley-type gas furnace at a heating rate of 8-10°C / min, a holding temperature of 950-970°C, a holding time of 2-3h, and is then cooled to below 300°C before being taken out of the furnace.